Paradoxical symbolism in Madurese fiction: A psychoanalytic perspective - Umamy, Etty; Supratno, Haris; Indarti, Titik (Edelweiss Applied Science and Technology, 2025)
This study aims to uncover the meaning of paradoxical symbols in Royyan Julian’s works, especially in the novel "Pendosa yang Saleh," using psychoanalytic and semiotic approaches. Through qualitative methods, data were collected through intensive reading of Julian’s works, interviews with literary experts and readers, and observations of social and cultural contexts. The analysis was conducted based on Jacques Lacan’s theory, which includes three main domains: real, imaginary, and symbolic. The results of the study indicate that paradoxical symbols such as Suhairiyah’s smile, hallucinations, and Mubarak’s behavior as a pedophile reflect the tension between social expectations and personal desires. These symbols enrich the narrative with multi-layered meanings that depict the psychological and moral complexities of the characters. This study contributes to the understanding of paradoxical symbols in fiction and offers insights for educators, writers, and psychological practitioners. The conclusion suggests that paradoxical symbols function as tools to depict internal and social conflicts in literary works, as well as providing recommendations for further research and practical applications in various media.